Glucose Supply Induces PsMYB2-Mediated Anthocyanin Accumulation in Paeonia suffruticosa ‘Tai Yang’ Cut Flower - Zhang, Lili; Yan, Li; Zhang, Chao; Kong, Xin; Zheng, Yiqing; Dong, Li (Frontiers in Plant Science, 2022)
Tree peony (Paeonia suffruticosa) is a well-known Chinese ornamental plant with showy flower color. However, the color fading problem during vase time seriously blocks its development in the cut flower market. In this study, we found that exogenous glucose supply improved the color quality of P. suffruticosa ‘Tai Yang’ cut flowers with increased total soluble sugar and anthocyanin contents of petals. Besides, the promotion effect of glucose was better than the osmotic control of 3-O-methylglucose (3OMG) treatment and the glucose analog mannose treatment. The structural genes, including PsF3H, PsF3′H, PsDFR, PsAOMT, and PsUF5GT, were remarkably upregulated under glucose treatment. Meanwhile, the regulatory genes, including PsbHLH1, PsbHLH3, PsMYB2, PsWD40-1, and PsWD40-2, also showed a strong response to glucose treatment. Among these five regulatory genes, PsMYB2 showed less response to 3OMG treatment but was highly expressed under glucose and mannose treatments, indicating that PsMYB2 may have an important role in the glucose signal pathway. Ectopic overexpression of PsMYB2 in Nicotiana tabacum resulted in a strong pigmentation in petals and stamens of tobacco flowers accompanied with multiple anthocyanin biosynthetic genes upregulated. More importantly, the overexpression of PsMYB2 enhanced the ability of glucose-induced anthocyanin accumulation in Arabidopsis thaliana seedlings since PsMYB2-overexpressing Arabidopsis showed higher expression levels of AtPAL1, AtCHS, AtF3H, AtF3′H, AtDFR, and AtLDOX than those of wild type under glucose treatment. In summary, we suggested that glucose supply promoted petal coloration of P. suffruticosa ‘Tai Yang’ cut flower through the signal pathway, and PsMYB2 was a key component in this process. Our research made a further understanding of the mechanism that glucose-induced anthocyanin biosynthesis of P. suffruticosa cut flowers during postharvest development, laying a foundation for color retention technology development of cut flowers.